Peran dan aPlikasi Wakaf dalam meWujudkan kesejahteraan umat di indonesia - Hazami, Bashlul (Analisis: Jurnal Studi Keislaman, 2016)
This research relates to the potential endowments as a force for the development of community’s welfare. Endowments are no longer synonymous with the land intended for educational institutions, cemeteries, places of worship or other, but endowments can also be used as a source of strength for community’s welfare and mobilize sectors of economic empowerment potential. The greater wealth and diversity of endowments that can be managed by nadzir professionally with proper management, the benefits gained from the management of waqf will be broader designation which in turn will strengthen the role of endowments in improving the economy and community’s welfare.